Efeitos da embalagem e do tempo de armazenamento sobre a intensidade de coloração do pó de pimentão (Capsicum annuum L.) - Stringheta, Paulo César; Teixeira Coelho, Dilson; Dias Casali, Vicente Wagner; Salustiano Pereira, Alonso (Revista Ceres, 2025)
This experiment was designed to study the effects of packaging materials and storage time on color retention of paprikas made from different varieties of red pepper (Capsicum annuum L.).